'Language of lies': Urgent issues and prospects in verbal lie detection research. (24th January 2019) - Nahari, Galit; Ashkenazi, Tzachi; Fisher, Ronald P.; Granhag, Pär‐Anders; Hershkowitz, Irit; Masip, Jaume; Meijer, Ewout H.; Nisin, Zvi; Sarid, Nadav; Taylor, Paul J.; Verschuere, Bruno; Vrij, Aldert
Abstract : Since its introduction into the field of deception detection, the verbal channel has become a rapidly growing area of research. The basic assumption is that liars differ from truth tellers in their verbal behaviour, making it possible to classify them by inspecting their verbal accounts. However, as noted in conferences and in private communication between researchers, the field of verbal lie detection faces several challenges that merit focused attention. The first author therefore proposed a workshop with the mission of promoting solutions for urgent issues in the field. Nine researchers and three practitioners with experience in credibility assessments gathered for 3 days of discussion at Bar‐Ilan University (Israel) in the first international verbal lie detection workshop. The primary session of the workshop took place the morning of the first day. In this session, each of the participants had up to 10 min to deliver a brief message, using just one slide. Researchers were asked to answer the question: 'In your view, what is the most urgent, unsolved question/issue in verbal lie detection?' Similarly, practitioners were asked: 'As a practitioner, what question/issue do you wish verbal lie detection research would address?' The issues raised served as the basis for the discussions that were held throughout the workshop. The current paper first presents the urgent, unsolved issues raised by the workshop group members in the main session, followed by a message to researchers in the field, designed to deliver the insights, decisions, and conclusions resulting from the discussions.